MATHEMATICAL MODELING OF THE INTENSIVE PLASTIC DEFORMATION WITH THE DESCRIPTION OF MICROSTRUCTURE EVOLUTION - Trusov, P.V.; Shveykin, A.I.; Volegov, P.S.; Kondratyev, N.S.; Yanz, A.Yu.; Makarevich, E.S.; Zoubko, I.Yu.; Sharifullina, E.R. (Perm Federal Research Centre Journal, 2014)
The article deals with the statement of the two-level model of polycrystalline materials inelastic deformation, including the description of the internal structure evolution. The paper puts forward the original version of the agreement conditions for defining relations of different scale levels, the proposed method of coordination also allows unambiguous definition derivative Cauchy stress tensor at the macro level which is independent of the reference system choice, and it is necessary for the formulation of constitutive relations for large deformations. Based on the physical analysis hardening laws and relations for crystal lattices rotations of crystallites are proposed. With the use of the developed algorithms on multi-level models for simple load cases experiments have been performed and the results of the calculations have been analyzed. It was found that these results are in good agreement with the experimental data. The problems associated with the formation of residual mesostresses in individual grains in the case of polycrystalline left in macro volume after its stress release are studied.